Kynurenine produced by indoleamine 2, 3-dioxygenase 2 exacerbates acute liver injury by carbon tetrachloride in mice. (30th May 2020) - Hoshi, Masato; Osawa, Yosuke; Nakamoto, Kentaro; Morita, Nanaka; Yamamoto, Yasuko; Ando, Tatsuya; Tashita, Chieko; Nabeshima, Toshitaka; Saito, Kuniaki
Highlights: Ido2 deficiency attenuated CCl4 -induced acute liver injury. Kynurenine production by Ido2 exacerbates progression of acute liver injury via Ahr signaling. Ido2 deficiency improved chronic inflammation after CCl4 treatment. Abstract: Kynurenine (Kyn) plays an important role as an immune check-point molecule and regulates various immune responses through its aryl hydrocarbon receptor (Ahr). Kyn is synthesized by indoleamine 2, 3-dioxygenase (Ido) and tryptophan 2, 3-dioxygenase (Tdo). Ido contributes approximately 90% of tryptophan catabolism. Although Kyn is increased in various liver disorders, the roles of Kyn in liver injury are complicated because Ido1, Ido2, and Tdo are activated in different cell types. In this study, the roles of Ido2 in carbon tetrachloride (CCl4 ; 1 ml/kg, i.p.)-induced acute liver injury were examined using Ido2 knockout mice and Ido2 inhibitor. After CCl4 treatment, the ratio of Kyn to tryptophan and levels of Kyn in the liver were increased, accompanied by activation of Ahr-mediated signaling, as revealed by increased nuclear Ahr and Cyp1a1 mRNA. Knockout of Ido2 (Ido2 −/− ) and treatment with Ido2 inhibitor 1-methyl-D-tryptophan (D-1MT; 100 mg/kg, i.p.) attenuated CCl4 -induced liver injury, with decreased induction of Ahr-mediated signaling. Administration of D-Kyn (100 mg/kg, i.p.) to Ido2 −/− mice canceled the effect of Ido2 deficiency and exacerbated acute liver damage by CCl4 treatment. In addition, liver fibrosis induced by repeated CCl4 administration was suppressed in Ido2 -/- mice. In conclusion, the action of Ido2 and Kyn in the liver may prevent severe hepatocellular damage and liver fibrosis.